Perancangan Video Dokumenter sebagai Media Penyampai Pesan Pelestarian Budaya Di Pesisir Desa Gisikcemandi - Asyhari, Hamam; Nisa, Diana Aqidatun (Universitas Pahlawan Tuanku Tambusai, 2024)
This study explains the important role of documentary videos as a medium for preserving local culture in Gisikcemandi Village. Through literature review and data analysis, documentary videos can contribute to maintaining, strengthening identity, and raising awareness of cultural heritage. Documentary videos can show real stories and can be published in digital media. That method. The method used is a mix method, namely qualitative and quantitative. Data collection techniques are carried out by interviews, focus group discussions, observations, and questionnaires. The results of the analysis stated that documentary video media is very suitable to be used to visualize culture, and tell the life of the coastal community of Gisikcemandi village. This study confirms the importance of documentary videos as a vital tool in promoting cultural diversity and building public awareness of valuable local values, thus providing a sustainable impact for the Indonesian nation.